Characterization of semi-refined carrageenan film plasticized with glycerol incorporated with Persicaria minor extract as antioxidant additives - Wan Yahaya, Wan Amnin; Hussaini, Nur Hazwani; Mohd Subakir, Farah Nurshahida; Mohd Azman, N. A. (IOP Publishing, 2020)
Semi refined carrageenan (2%w/w) plasticized with 0.9% (w/w) glycerol (G) added with Persicaria minor (PM) extract and 0.4% (w/w) BHA as antioxidant additives for the development of active packaging films. The extraction of PM using 75% (v/v) ethanol: water ratio showed the highest polyphenol content with 176.80±4.37 Gallic Acid Equivalent (GAE)/L sample and 94.65±0.17% inhibition analyzed using DPPH antioxidant activity (p<0.05). The characterization of SRC-G based film containing 0.4, 1.0, 1.5 and 2.0% (w/w) PM and BHA were observed using FTIR, mechanical and physical properties of the treated films. FTIR spectrum band showed insight analysis of PM extract and BHA with carrageenan. SRC film plasticized with glycerol improved overall physical properties including thickness, barrier and flexibility and increased tensile strength and elongation at break compared to the SRC film only (p<0.05). The active films with PM extracts (2.0% w/w) exhibited good mechanical properties with tensile strength and elongation at break with 28.01±0.17 and 37.37±0.29 respectively (p<0.05). The addition of PM extract in SRC films increased the moisture content and opacity as proportionally to the concentration of PM extracts. Film treated with 2.0% PM showed lowest value of films solubility compare to all sample (p<0.05). Hence, the characterization measurement of SRC based films demonstrated great potential with natural extract formulation for the development of active film packaging for food products.